Till Debt Do Us Part: A Failed Marriage - Alonso, Ruperto; Canlas, Dante; Fabella, Raul; Medalla, Felipe; Paderanga, Jr., Cayetano (Kasarinlan: Philippine Journal of Third World Studies, 2009)
The agreement that the Philippine signed in July 1987 with commercial bank creditors was borne out of a negotiating failure on part of the Philippines. An effective approach to debt negotiations should have had the following elements: (a) a focus on net resource flows; (b) a contingent agreement that links net resource flows to economic conditions; (c) a distinction between old debt and new that gives seniority to new loans; and (d) a new negotiating team unencumbered with baggage from the past.